Repressions against the families of participants of resistance in Western Ukraine (1944–1952) - Vronskaja, Tamara (Genocidas ir rezistencija, 2008)
The repressive deportations of 1944–1952 took on a massive and brutal character in Western Ukraine, whose population was actively involved in the national liberation movement. They began in the first months of the Second World War and took place in the spring of 1944, when the liberation of Ukraine from Hitler’s occupiers was still a long way off. Already then, the party leaders in many official documents began to threaten women and children with repression, openly stating that they would use family hostage-taking alongside armed methods to achieve their desired goal of turning western Ukraine into a 100 per cent Soviet country.
Keywords: Ukraine; resistance; Soviet occupation; repressions